2010
DOI: 10.1002/app.31880
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the effect of adhesion properties of PEEK modified by atmospheric pressure plasma and low pressure plasma

Abstract: High performance polymer, Polyether Ether Ketone (PEEK) (service temperature À250C to þ300 C, tensile strength: 120 MPa) is gaining significant interest in aerospace and automotive industries. In this investigation, attention is given to understand adhesion properties of PEEK, when surface of the PEEK is modified by two different plasma processes (i) atmospheric pressure plasma and (ii) low pressure plasma under DC Glow Discharge. The PEEK sheets are fabricated by ultra high temperature resistant epoxy adhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…A constant plasma current of 110±0.5 mA was maintained to achieve moderately high power plasma. The discharge voltage applied for the given electrode separation of 6 cm at 0.2 mbar was sufficient to ionize the Oxygen, Nitrogen and Argon in air [14][15][16]. Hence, multicomponent and collisional plasma was produced showing a distinct glow.…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…A constant plasma current of 110±0.5 mA was maintained to achieve moderately high power plasma. The discharge voltage applied for the given electrode separation of 6 cm at 0.2 mbar was sufficient to ionize the Oxygen, Nitrogen and Argon in air [14][15][16]. Hence, multicomponent and collisional plasma was produced showing a distinct glow.…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…Properties of Adhesive Bonded Polymer Joint Earlier investigation [23] reveals that surface energy of PEEK when exposed to low pressure plasma for 120 sec attains to the maximum up to 65.54 mJ/m 2 and when exposed to atmospheric pressure plasma for 30 sec attains its maximum value up to 73.44 mJ/m 2 . Therefore, in this investigation, lap shear tensile strength is correlated to the maximum values of sur face energy obtained from low pressure plasma and atmospheric pressure plasmas and shown in Fig.…”
Section: Effect Of Surface Energy On the Lap Shear Tensilementioning
confidence: 99%
“…The increase in surface energy of polymer is usually correlated with the adhesive bonded joint strength and it is important to note that in number of cases atmo spheric pressure plasma is more capable than low pres sure plasma [23]. In this context Hobson et al [24] have revealed that when PBI surface has been modi fied under an electron beam, the IR (ATR) spectros copy shows generation of CO 2 H units at the site of the polymer backbone and the concurrent loss of fluorine groups (-OCF 2 -C(CF 3 )-F-) n -OCF 2 CF 2 -SO 3 H into the side chain, leading to significant increase in hydrophilic properties of the polymer and it could be possible that atmospheric pressure plasma also plays similar role.…”
Section: Effect Of Surface Energy On the Lap Shear Tensilementioning
confidence: 99%
“…This results in considerable improvement of adhesive bond strength. Recent studies have shown that atmospheric pressure plasma is more capable than low-pressure plasma in terms of surface modifi cation of PEEK [9] ; however, it is not clear whether the same principle is also applicable for other polymers.…”
Section: Introductionmentioning
confidence: 94%
“…Based on these considerations, the present investigation was carried out on other ultra-high temperature resistant polymeric sheets such as PBI sheets, to justify the statement given in the above reference [9] . PBI is fabricated by using recently developed ultra-high temperature resistant epoxy adhesive (DURALCO 4703) which can retain its cohesive properties even when exposed to cryogenic atmosphere.…”
Section: Introductionmentioning
confidence: 97%